Challenges and Opportunities: Implementation of the Electronic Divorce Certificate (EAC) Regulation at the Pulang Pisau Religious Court - Kartini, Kartini (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2026)
The implementation of the Electronic Divorce Certificate (EAC) since 1 July 2025 is part of the digital transformation of the judiciary aimed at realizing the principles of simplicity, speed, and low cost. However, its implementation at the Pulang Pisau Religious Court still faces various obstacles, particularly those related to public digital literacy. Of the 41 EACs issued, 58.54% of litigants still came to the court to request technical assistance, due to difficulties in logging into email accounts, limited internet access, the absence of bank accounts for the payment of Non-Tax State Revenue (PNBP), and unfamiliarity with the use of technology. This empirical legal study analyzes the challenges and opportunities of EAC implementation through interviews, observations, and documentation studies, grounded in the Theory of Legal Effectiveness and Prismatic Theory. The results indicate that the main challenges lie in the digital divide, technical constraints, and both user and internal institutional competencies. Nevertheless, EAC presents opportunities in the form of service efficiency, increased transparency, accelerated public access, and the strengthening of the judiciary’s institutional image. These findings underscore the need to enhance public outreach, improve infrastructure, and provide sustained technical support so that EAC implementation can be optimized and truly support the modernization of judicial services.